2008
DOI: 10.1111/j.1365-2966.2008.13111.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric accretion on the T Tauri star BP Tauri

Abstract: From observations collected with the ESPaDOnS and NARVAL spectropolarimeters, we report the detection of Zeeman signatures on the classical T Tauri star BP Tau. Circular polarisation signatures in photospheric lines and in narrow emission lines tracing magnetospheric accretion are monitored throughout most of the rotation cycle of BP Tau at two different epochs in 2006. We observe that rotational modulation dominates the temporal variations of both unpolarised and circularly polarised spectral proxies tracing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
141
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(156 citation statements)
references
References 38 publications
12
141
3
Order By: Relevance
“…Observations of magnetically sensitive absorption lines in TTSs, however, have shown that most TTSs have complex surface field geometries (Johns-Krull et al 1999;Valenti & Johns-Krull 2004;Daou et al 2006;Donati et al 2008Donati et al , 2011aDonati et al , 2011bDonati et al , 2011c. JG02 show that if the dipolar field requirement is relaxed, but that the amount of magnetic flux participating in the accretion flow is conserved and mapped back to the stellar surface from the truncation point (this is equal to one-third of the total magnetic flux trapped at the truncation radius; see OS95 for details), then the OS95 model can be modified to predict the following relationship:…”
Section: Johnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of magnetically sensitive absorption lines in TTSs, however, have shown that most TTSs have complex surface field geometries (Johns-Krull et al 1999;Valenti & Johns-Krull 2004;Daou et al 2006;Donati et al 2008Donati et al , 2011aDonati et al , 2011bDonati et al , 2011c. JG02 show that if the dipolar field requirement is relaxed, but that the amount of magnetic flux participating in the accretion flow is conserved and mapped back to the stellar surface from the truncation point (this is equal to one-third of the total magnetic flux trapped at the truncation radius; see OS95 for details), then the OS95 model can be modified to predict the following relationship:…”
Section: Johnsmentioning
confidence: 99%
“…Measurements of mean surface magnetic fields on CTTSs have shown the field strengths to be relatively constant from star to star (Johns-Krull et al 1999;Guenther et al 1999;Valenti & Johns-Krull 2004;Johns-Krull 2007;Yang & JohnsKrull 2011). Donati et al (2011b) have suggested, however, that the strength of the dipole and octopole components of the magnetic field on TTSs can vary strongly from star to star depending upon the existence and extent of a star's radiative core: fully convective stars host strong, stable dipolar fields (e.g., Donati et al 2008Donati et al , 2010 while stars with small radiative cores (0.0 < M core /M * 0.4) tend to have weaker dipolar fields and more dominant octopolar field components (Donati et al 2011a(Donati et al , 2011b. For example, Donati et al (2008Donati et al ( , 2010) measure 1.2 and 2-3 kG dipolar magnetic field components on the fully convective CTTSs BP Tau and AA Tau, respectively; for the partially convective CTTSs V2129 Oph and V4046 Sgr, however, Donati et al (2011a) measure 900 and 50-100 G dipolar magnetic field components, respectively, for each star.…”
Section: Johnsmentioning
confidence: 99%
“…Young solar type stars (ages of a few Myr), called T Tauri stars, also undergo a fully convective phase. Strong magnetic fields are detected on these objects both in unpolarised spectroscopy (e.g., Johns-Krull 2007) and in spectropolarimetry (e.g., Donati et al 2008a). It is likely that these objects generate their magnetic fields through dynamo processes similar to those acting in main sequence M dwarfs.…”
Section: Magnetic Fields Of Young Sunsmentioning
confidence: 99%
“…However, it is more likely that the asymmetry of the outflows arises from the asymmetry of the star's magnetic field. Substantial observational evidence points to the fact that young stars often have complex magnetic fields consisting of dipole, quadrupole, and higher order poles misaligned with respect to each other and the rotation axis (Jardine et al [86]; Donati et al [87]). Analysis of the plasma flow around stars with realistic fields have shown that a significant fraction of the star's magnetic field lines are open and may carry outflows (Gregory et al [88]).…”
Section: Lopsided Jets and Outflows From Discsmentioning
confidence: 99%